2018
DOI: 10.1038/s41598-018-20642-4
|View full text |Cite
|
Sign up to set email alerts
|

Altered DNA methylation indicates an oscillatory flow mediated epithelial-to-mesenchymal transition signature in ascending aorta of patients with bicuspid aortic valve

Abstract: Disturbed flow has been suggested to contribute to aneurysm susceptibility in bicuspid aortic valve (BAV) patients. Lately, flow has emerged as an important modulator of DNA methylation. Hear we combined global methylation analysis with in vitro studies of flow-sensitive methylation to identify biological processes associated with BAV-aortopathy and the potential contribution of flow. Biopsies from non-dilated and dilated ascending aortas were collected from BAV (n = 21) and tricuspid aortic valve (TAV) patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…Thus, the immaturity in BAV can turn into premature senescence with all accompanying consequences. Our collective data on differentially regulated pathways between BAV and TAV i.e., hypoxia, oncogene-related pathways such as WNT or MYC, and UV response may well be due to premature senescence (16,110,111), giving support to the possibility of EndMT/EMT conversion to senescence and aortic degeneration in BAV. Compatible with shorter telomeres and senescence-induced activation of cell cycle checkpoint, we also observed significantly increased protein expression of the cyclindependent kinase inhibitor P27 (the product of CDKN1B gene) in non-dilated BAV AscA (16).…”
Section: Premature Aging and Bav Aortopathymentioning
confidence: 59%
See 1 more Smart Citation
“…Thus, the immaturity in BAV can turn into premature senescence with all accompanying consequences. Our collective data on differentially regulated pathways between BAV and TAV i.e., hypoxia, oncogene-related pathways such as WNT or MYC, and UV response may well be due to premature senescence (16,110,111), giving support to the possibility of EndMT/EMT conversion to senescence and aortic degeneration in BAV. Compatible with shorter telomeres and senescence-induced activation of cell cycle checkpoint, we also observed significantly increased protein expression of the cyclindependent kinase inhibitor P27 (the product of CDKN1B gene) in non-dilated BAV AscA (16).…”
Section: Premature Aging and Bav Aortopathymentioning
confidence: 59%
“…(48). Lastly, DNA methylation studies further showed enrichment of EMT genes in non-dilated AscA of BAV patients (111). Similarly, analysis of intima-media in dilated AscA of BAV and TAV patients identified EMT as the top GO term and several key transcription factors for EMT, including ZEB1, SNAI2, and TWIST2, were hypomethylated in dilated BAV aorta.…”
Section: Non-physiological Shear Stress and Induction Of Endmt/emtmentioning
confidence: 83%
“…We found that LPS-challenged cells underwent a significant increase in the global DNA methylation profile paralleled by a significant decrease in global hydroxymethylation ( Figure 7 a). Emerging evidence suggests that DNA methylation and hydroxymethylation variations are required for EMT [ 47 , 48 , 49 ], a multistep and progressive phenomenon, consisting of loss of the epithelial and acquisition of a mesenchymal phenotype, associated with cell transformation, playing a major role in a variety of diseases, including airway remodeling in asthma [ 26 , 50 ] and cancer [ 17 , 50 ]. Hence, we subsequently investigated whether the LPS-challenged cells exposed to AuNPs could undergo EMT and whether this transformation could be causatively linked to the observed MG-H1 accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…Again, AG treatment prevented both epigenetic modifications, suggesting a causative role of MG-dependent glycative stress in triggering these processes in LPS-challenged AuNPs-exposed BEAS-2B and A549 cells. Emerging evidence suggests that global DNA methylation and hydroxymethylation variations are required for EMT [ 47 , 48 , 49 ]. Since we found that MG-H1 controlled both DNA global modifications and EMT, we speculate that this MG-derived AGE can be an additional agent linking these two phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Other mutated gene often correlated with specific features and prognosis. Due to abnormal flow in BAV aneurysm, the aberrant methylation of epithelial-mesenchymal-transition and increased expression of WNT/β-catenin genes like MYLK, ZEB1 were involved (Bjorck et al, 2018). Besides, transcriptome analyses and immunohistochemical study of ascending aortic specimens from BAV patients showed that receptor tyrosine kinase (RTK)/p-AKT pathway in the middle part of ascending aortic wall was activated, in spite of the constant expression level of total AKT (Hirata et al, 2018; Yamashita et al, 2018).…”
Section: Genetics: Polymorphism and Complexity Of The Pathogenesismentioning
confidence: 99%